Contribution of dermal ethanol absorption during laboratory-controlled high-frequency use of alcohol-based hand rubs followed by glove use - Paul T. J. Scheepers; Kirsten Lassing; Martien H. F. Graumans; Sander H. P. Driessen; Antzelina Gkintsev; Ioanna Konstantinou; Valérie Leermakers; Hilde Onstek; Maxime Sülter; Lotte van den Oord; Chariya van Dolder; Hendrik Jan Jansen; et al. (Archives of Toxicology, 2026)
The safety of using ethanol-based products for hygienic hand disinfection in healthcare workers is controlled by restricting air levels. This raises the question of whether these workers are sufficiently protected against potential dermal absorption. The study aim was to determine the contribution of the dermal route to the total uptake of ethanol. A laboratory-controlled study of 25 sequential alcohol-based-hand-rubs (ABHRs) with subsequent intermediate glove use was conducted in seven healthcare workers. Two exposure conditions were compared: hands and forearms placed inside a laboratory fume hood preventing inhalation (skin-only condition) and the same procedure but outside the fume hood to allow inhalation (native condition). The hand hygiene product contained 84% ethanol and 1% ethanol-d6 added to verify exogenous origin. Inhalation exposure was measured by personal air sampling. Blood was collected at baseline, during exposure and a post-exposure wash-out period and analysed for ethanol and ethanol-d6 by HS-GC-MS. The contribution of dermal uptake was assessed by comparing the area-under-curve (AUC) of blood ethanol concentrations in the skin-only condition with that in the native condition within each study participant. Inhalation exposure in the breathing zone was (mean ± sd): 5.3 ± 3.6 mg/m 3 in the skin-only condition and 120 ± 7 mg/m 3 in the native condition. The corresponding AUCs for blood ethanol concentrations were 1400 ± 1100 and 3300 ± 2300 (mg/L)*min ( p = 0.014), respectively, indicating a contribution from dermal absorption of 43 ± 28% ( N = 7). For ethanol-d6 these values were 17 ± 4 and 48 ± 17 (mg/L)*min ( p = 0.064), respectively, with a contribution of dermal uptake of 40 ± 16% ( N = 3). In conclusion, high-frequency ABHRs lead to significant dermal absorption of ethanol.

Instability and blood flow restriction: do they contribute to resistance training adaptations? - Murilo César Carvalho Christ; Leonardo Carvalho; Gabriel Truffi; Vinícius Concon; Rafaela Sander; Adriano Serra; Jeremy P. Loenneke; Renato Barroso (German Journal of Exercise and Sport Research, 2026)
The aim of this study was to investigate changes in muscle size, strength, and dynamic balance after resistance training on an unstable surface with and without blood flow restriction and on a stable surface. Twenty-nine untrained men were assigned according to baseline vastus lateralis muscle thickness to one of the three resistance training groups: stable surface (TRAD), unstable surface (UST), and unstable surface with blood flow restriction (UST-BFR). Each group performed three sets of 8–12 repetition maximum (RM) in the back squat and the leg press 45° exercises. Vastus lateralis muscle thickness, back squat and leg-press 1‑RM and dynamic balance were assessed before and after 8 weeks of training. Two-way repeated measures analysis of covariance (ANCOVA), having group as a factor and prevalues as covariates, was used to analyze muscle thickness, 1‑RM, and dynamic balance. Significance level was set at p ≤ 0.05. Groups were not different at posttraining for any variable, except dynamic balance, where UST improved over TRAD ( p = 0.019). Based on these findings, we propose that strength and conditioning coaches and practitioners should consider incorporating resistance training on unstable surfaces to enhance dynamic balance while still achieving gains in muscle size and strength.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Designing a rapid response process for urgent policy-relevant knowledge needs: A case study on deadwood and forest fires - R. Dianoux; L. Brotons; S. Corticeiro; J.-C. Dajka; U. Jacob; K. Korhonen-Kurki; M. Larjavaara; K. Locher-Krause; A.B. Leverkus; P. Maia; T.G.M. Sanders; M. Vandewalle; et al. (Environmental Science & Policy, 2026)

WaterLANDS: A Database of Carbon Stocks, GHG Fluxes and Biodiversity Indicators in Restored European Wetlands - Irene Ascenzi; Jur Seuren; Sander van der Hooft; Gert‐Jan van Duinen; Gustaf Granath; Jelle P. Hilbers; Joseph Holden; Milena Holmgren; Mark A. J. Huijbregts; Marieke M. van Katwijk; Juul Limpens; Shane McGuinness; et al. (Global Ecology and Biogeography, 2026)
Motivation Wetland restoration is expected to play an important role in helping Europe achieve its climate and biodiversity targets as stated in the European Green Deal. Restored wetlands sequester atmospheric carbon and provide habitat for a wide range of plant and animal species. To design effective, evidence‐based restoration targets and guide future projects, it is critical to understand the impacts of wetland restoration on a diverse range of ecosystem functions. Existing knowledge, however, is scattered across empirical studies assessing restoration outcomes on a limited set of indicators, in specific settings and single locations. This fragmentation limits our ability to assess the effectiveness of wetland restoration across different indicators and contexts. To address this gap, we present a comprehensive dataset on the effects of wetland restoration across Europe. The dataset compiles 2534 entries representing changes in carbon stocks, greenhouse gases (GHG) fluxes, and biodiversity indicators across different wetland types, pre‐restoration land use and restoration strategies. The database allows comparisons between restored and both degraded and pristine sites. Main Types of Variables The database contains data on carbon stock, GHG fluxes and biodiversity indicators in restored and control wetlands, with standard error, sampling methodology, wetland type, location, climate, restored site area, water table depth, soil characteristics, pre‐restoration land use, time since restoration started, and restoration strategy. Spatial Location and Grain Europe. Time Period and Grain Original data were published between 2000 and 2024. Restoration age ranges from a few months to 139 years. Major Indicators and Level of Measurement Carbon stocks, GHG fluxes and biodiversity indicators in restored wetlands and two controls: degraded and pristine sites. Software Format The dataset is available at https://doi.org/10.17026/LS/H5MFEH as a .xlsx file and as a .shp file, with a metadata file.

Lethal Sycamore maple intoxication in a grazing three-month-old foal - N. Janzen; J. Sander; M. Terhardt; M. Mallek; H Smith; P. Witt; M.J.P. Theelen (Journal of Equine Veterinary Science, 2025)

Extreme temperatures, recent warming and seasonal influenza-linking human exposures to respiratory health in southern Germany - Matteo Boser; Daria Luschkova; Monika Seemann; Monika Seemann; Gertrud Hammel; Anna Lang; Julia Sander; Iñaki Soto Rey; Markus Wehler; Katharina Zeiser; Claudia Traidl-Hoffmann; Maria P. Plaza (International Archives of Occupational and Environmental Health, 2025)
Purpose In the context of climate change, extreme ambient temperatures pose a major threat to human health. This study aims to provide detailed insights into how extreme temperatures and potential confounders affect respiratory morbidity. Methods We employed a 14-year time series analysis (2006–2019) in southern Germany, applying penalized distributed lag non-linear models to estimate exposure–response relationships between extreme temperatures and respiratory health outcomes, considering emergency outpatient treatments and hospital admissions at the emergency department of the University Hospital Augsburg. We thereby explored the roles of relative humidity and seasonal influenza as potential confounders and vulnerabilities related to age and gender. Results We found significantly elevated relative risks (RRs) for the short-term cumulative effect (Lag: 0–3 days) of extreme heat and the long-term cumulative effect (Lag: 0–21 days) of extreme cold on outpatient treatments and hospital admissions. Seasonal influenza was identified as a significant confounder, with attributable fractions comparable to those of cold temperatures. A sub-period analysis (2006–2012 and 2013–2019) revealed a correlation between the recent rise in temperature and the strong increase in the estimated short-term cumulative effect of extreme heat on hospital admissions (2006–2012, RR: 1.08 (95%CI [0.91, 1.27]) vs. 2013–2019, RR: 1.32 (95%CI [1.15, 1.51]). Conclusion Our study demonstrated that extreme temperatures significantly affect respiratory morbidity, with notable influences from seasonal influenza. Sub-period analysis indicated that rising temperatures are already translating into measurable effects on respiratory health, foreshadowing the potentially devastating impacts of global warming on human health. Our results thereby provide highly relevant insights to support targeted public healthcare interventions.

The association of cigarette smoking with appetite, appetite-related hormones and food reward: a matched-pair cohort study - Arwa Alruwaili; Ridah Nayeemullah; Buket Engin; Sundus Malaikah; Lynsey James; James P. Sanders; David Thivel; Alice E. Thackray; David J. Stensel; James A. King; Scott A. Willis (Appetite, 2025)

Winter flood significantly changes salinity and nutrient export from land to sea - Ingeborg Bussmann; Holger Brix; Götz Flöser; Philipp F. Fischer; Saranya Jayachandran; Eric P. Achterberg; Kristine Carstens; Inga V. Kirstein; Tina Sanders; Björn Raupers; Yoana Voynova; Norbert Kamjunke (Frontiers in Marine Science, 2025)
Flood events caused by high rainfall can have profound biogeochemical impacts on riverine systems but also on the receiving coastal waters. The winter flood in Germany in December 2023/January 2024 affected the Elbe and Weser River systems. We obtained unique data during the peak of the flood and compared these with the monthly means from previous years (2018-2023). Hydrographic parameters and nutrients were determined by standard methods. Low salinity values were observed in the Elbe estuary and the adjacent German Bight (part of North Sea). At Helgoland the lowest average salinity was observed in January 2024 with 31.3 ± 0.5 compared to an average salinity of 32.7 ± 0.7 for the years 2016 to 2023. Nutrient loads (nitrate, phosphate) in the rivers showed a six- to 11-fold increase in the Elbe and Weser rivers compared to years without flood events. Enhanced concentrations of nitrate and silicate were found in the German Bight in January. Nutrients were diluted with North Sea waters, indicating a conservative behavior of nutrients in winter. Atypical prevailing meteorological conditions in January 2024, with predominantly easterly winds, potentially affect the dispersal of the river plume and the nutrients in the North Sea. In March 2024 the chlorophyll-a concentration strongly increased to 2.9 ± 1.8 µmol/L and was twice as high compared to only 1.5 ± 0.7 µmol/L observed in previous years. The observed intensified spring bloom in March in the German Bight near the island of Helgoland indicates the impacts of the flood-derived nutrient inputs three months after the flood event, as the timing of light and nutrient availability was optimal. It is assumed that seasonality and magnitude of flooding in the Elbe estuary and adjacent coastal region will change in future due to climate warming. Thus, the timing of light and nutrient availability will also change, with unconstrained impacts on primary producers and higher trophic levels.

An assessment of maternal concentrations of per- and polyfluoroalkyl substances (PFAS) and trace elements during the second trimester of pregnancy in western Pennsylvania - Natalie F. Price; Alexis Kiyanda; Wan-Yee Tang; Zachary Zimmerman; Janet Catov; Aaron Barchowsky; Aubrey L. Galusha; Kurunthachalam Kannan; Elizabeth J. Mullin; Patrick J. Parsons; Nesta Bortey-Sam; Alison P. Sanders (Environmental Monitoring and Assessment, 2025)

The first report of quadricuspid aortic valve in cattle: clinical, anatomical and histological findings in three Holstein cattle - Samuel Kalpers; Sander Prins; Katherine Ings; Jayne Orr; Mark P. Dagleish (Journal of Comparative Pathology, 2025)

Metal mechanisms of mitochondrial toxicity: recent review of arsenic, cadmium, and lead-induced nephrotoxicity - Rachel E. Turkington; Neil A. Hukriede; Jacqueline Ho; Nishad Jayasundara; Alison P. Sanders (Environmental Science and Pollution Research, 2025)

Short communication: catechol-O-methyltransferase allelic variation in relation to psychological and hormonal indices of stress in children and adolescents with chromosome 22q11.2 deletion syndrome (22q11.2DS) - Jessie L. Beebe; Cydney R. Martin; Ashley F. P. Sanders; Jeremy Guidry; Fahad Faheem; Joel Atallah; Elliott A. Beaton (Journal of Applied Genetics, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

An exploration of the perspectives of Dutch adults experiencing a genetic condition on human germline gene editing - S. Jeanne A. N. Arnold; Diewertje Houtman; Isabel R. A. Retel Helmrich; Sander R. Hilberink; Sam R. Riedijk; D. Arets; S. van Baalen; B. van Beers; B. Burgers; M. C. Cornel; C. G. van El; W. P. Geuverink; et al. (Journal of Community Genetics, 2025)
Views of people with a genetic condition are crucial in deliberations on human germline gene editing (HGGE), but their perspectives are at risk to be devalued due to epistemic injustice and insufficient attention for the possible sensitivities surrounding HGGE. This study set out to explore the perspectives of people dealing with a genetic condition regarding HGGE, and the possible sensitivities surrounding this topic. We conducted a 2-phase qualitative interview ( N = 29) and focus group study ( N = 9) on the perspectives of people with or carrying a genetic condition and family members regarding HGGE. Insights from the interviews were used in the organization of the focus groups. We included 38 persons who have experiences with 18 different genetic conditions. Three main themes were identified: personal deliberation on HGGE, HGGE in the context of reproductive decision making and the impact of HGGE on society. Participants stated discussing the topic was controversial, complicated and overwhelming. An informal setting with peer support helped them to process their thoughts and feelings. This study found three main conclusions. First, the perspectives on HGGE are highly influenced by the perception of a genetic condition as a burden or as part of an identity. Secondly, in the deliberation on HGGE, many participants experienced a conflict between accepting a genetic condition and taking action to mitigate potential harm. Thirdly, the subject and object of the deliberation on HGGE mattered: for whom and what for? Moreover, this study has yielded pragmatic recommendations to accommodate sensitivities around discussing HGGE.

Conodonts suggest a late Spathian (late Early Triassic) age for Thaisaurus chonglakmanii (Reptilia: Ichthyosauromorpha) from Thailand - Si-Yao Ye; Kui Wu; Zuo-Yu Sun; P. Martin Sander; Adun Samathi; Yuan-Yuan Sun; Cheng Ji; Varavudh Suteethorn; Jun Liu (Palaeoworld, 2025)

Migratory Birds Advance Spring Arrival and Egg‐Laying in the Arctic, Mostly by Travelling Faster - Thomas K. Lameris; Michiel P. Boom; Rascha J. M. Nuijten; Nelleke H. Buitendijk; Götz Eichhorn; Bruno J. Ens; Klaus‐Michael Exo; Petr M. Glazov; Sveinn Are Hanssen; Philip Hunke; Henk P. van der Jeugd; Margje E. de Jong; et al. (Global Change Biology, 2025)
In the current warming climate, many organisms in seasonal environments advance their timing of reproduction to benefit from resource peaks earlier in spring. For migrants, the potential to advance reproduction may be constrained by their migration strategies, notably their ability to advance arrival at the breeding grounds. Recent studies show various changes in migration strategies, including wintering closer to the breeding grounds, earlier departure from the wintering grounds or faster travels by spending less time at stopover sites. However, whether such changes lead to earlier arrival or earlier breeding remains an open question. We studied changes in migration and reproduction timing in 12 populations of nine migratory birds, including seabirds, shorebirds, birds of prey and waterfowl breeding at Arctic sites bordering the Greenland and Barents Sea, a region undergoing rapid climate warming. The timing of migration and reproduction was derived from tracking and field data and analysed to study (1) how timing has changed in response to the changing moment of snowmelt at the breeding grounds and (2) what adjustments in migration strategies this involved. We found that in years with early snowmelt, egg‐laying in multiple populations advanced, but only two waterfowl populations also advanced arrival in the Arctic. In contrast, arrival in the Arctic generally advanced with time, even when snowmelt or egg‐laying dates did not advance. Earlier arrival with time was mostly explained by populations traveling to the Arctic faster, likely spending less time at stopover sites. Inability to forecast conditions in the Arctic may limit birds to adjust migration timing to annually varying snowmelt, but we show that several species, particularly waterfowl, are able to travel faster and advance the timing of migration over the years. The question remains whether this reflects adaptations to Arctic climate change or other factors, for example, environmental changes along the migratory route.

Effects of extreme drought on the invasion dynamics of non-native plants - Shareen K.D. Sanders; Mark van Kleunen; Eric Allan; Madhav P. Thakur (Trends in Plant Science, 2025)

Characterizing pyrethroid and fipronil concentrations in biosolids - John Wheeler; Gabrielle P. Black; Michelle L. Hladik; Corey J. Sanders; Jennifer Teerlink; Luann Wong; Xuyang Zhang; Robert Budd; Thomas M. Young (Science of The Total Environment, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Novel Curvularia species causing disseminated phaeohyphomycosis in a dog - Jared A. Jaffey; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Carmita J. Sanders; Jason D. Struthers; Annalise Black; BinXi Wu; Kara S. Thomas; Patricia Bennett; Jessica Watt (Topics in Companion Animal Medicine, 2025)

Development of Zinc-Containing Chitosan/Gelatin Coatings with Immunomodulatory Effect for Soft Tissue Sealing around Dental Implants - Jing Han; Jorine G. F. Sanders; Lea Andrée; Bart A. J. A. van Oirschot; Adelina S. Plachokova; Jeroen J. J. P. van den Beucken; Sander C. G. Leeuwenburgh; Fang Yang (Tissue Engineering and Regenerative Medicine, 2025)
BACKGROUND: Soft tissue integration (STI) around dental implant abutments is a prerequisite to prevent bacterial invasion and achieve successful dental implant rehabilitation. However, peri-implant STI is a major challenge after dental abutment placement due to alterations in the immune microenvironment upon surgical dental implant installation. METHODS: Based on known immunomodulatory effects of zinc, we herein deposited zinc/chitosan/gelatin (Zn/CS/Gel) coatings onto titanium substrates to study their effect on macrophages. First, we exposed macrophages to cell culture media containing different zinc ion (Zn 2+ ) concentrations. Next, we explored the immunomodulatory effect of Zn/CS/Gel coatings prepared via facile electrophoretic deposition (EPD). RESULTS: We found that Zn 2+ effectively altered the secretome by reducing the secretion of pro-inflammatory and enhancing pro-regenerative cytokine secretion, particularly at a Zn 2+ supplementation of approximately 37.5 μM. Zn/CS/Gel coatings released Zn 2+ in a concentration range which effectively stimulated pro-regenerative macrophage polarization as demonstrated by M2 macrophage polarization. Additionally, the impact of these Zn 2+ -exposed macrophages on gingival fibroblasts incubated in conditioned medium showed stimulated adhesion, proliferation, and collagen secretion. CONCLUSION: Our promising results suggest that controlled release of Zn 2+ from Zn/CS/Gel coatings could be applied to immunomodulate peri-implant STI, and to enhance dental implant survival.

Immunohistochemical characterization of interstitial cells and their spatial relationship to motor neurons within the mouse esophagus - Emer P. Ni Bhraonain; Jack A. Turner; Karen I. Hannigan; Kenton M. Sanders; Caroline A. Cobine (Cell and Tissue Research, 2025)

Effects of elevated CO2 on the critical oxygen tension (Pcrit) and aerobic metabolism of two oxygen minimum zone (OMZ) hypoxia tolerant squat lobster species - Erika Jorquera; Antonio Brante; Ángel Urzúa; Trystan Sanders; Robert P. Ellis; Rod Wilson; Mauricio A. Urbina (Science of The Total Environment, 2024)

Soil greenhouse gas fluxes partially reduce the net gains in carbon sequestration in mangroves of the Brazilian Amazon - Angelo F. Bernardino; Hermano M. Queiroz; Gabriel N. Nobrega; Gabriel C. Coppo; Christian J. Sanders; Antonio E.B. Silva; J. Boone Kauffman; Rodolfo F. Costa; Carla F. Pacheco; André Vassoler; Araiene P. Pereira; Francisco Ruiz; et al. (Environmental Research, 2024)

Corrigendum to Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva [Environ. Res. 216P4 (2023) 114846] - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2024)

Fossilization and low-grade metamorphism of Triassic marine reptiles from southwest China: A continuum of apatite transformation and fluorite precipitation - Qiang Li; Jun Liu; Fabian Gäb; P. Martin Sander (Chemical Geology, 2024)

Arctic Alaska deepwater organic carbon burial and environmental changes during the late Albian–early Campanian (103–82 Ma) - Richard O. Lease; Katherine J. Whidden; Julie A. Dumoulin; David W. Houseknecht; Palma J. Botterell; Mark F. Dreier; Neil P. Griffis; Roland Mundil; Andrew R.C. Kylander-Clark; Margaret M. Sanders; John W. Counts; Jean M. Self-Trail; et al. (Earth and Planetary Science Letters, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Intraspecific competition hinders drought recovery in a resident but not in its range-expanding congener plant independent of mycorrhizal symbiosis - Shareen K. D. Sanders; Ludovico Formenti; Micha Fahrni; Madhav P. Thakur (Plant and Soil, 2024)
Background and aims Understanding biotic interactions within plant populations and with their symbiotic partners is crucial for elucidating plant responses to drought. While many studies have highlighted the importance of intraspecific plant or mutualistic fungal interactions in predicting drought responses, we know little about the combined effects of these two interactions on the recovery of plants after drought. Methods We conducted an experiment to study the recovery after an extreme drought event of a native European plant species ( Centaurea jacea ) and its range-expanding congener ( Centaurea stoebe ), across a gradient of plant density and in association with an AM fungal species ( Rhizophagus irregularis ). Results Our results showed strong intraspecific competition in C. jacea , which constrained their post-drought recovery. We further found that AM fungi constrained root biomass recovery of C. jacea after drought under high intraspecific competition. The post-drought recovery in C. stoebe was high potentially due to its greater plasticity in the root diameter under drought conditions. Conclusion Strong intraspecific competition can constrain recovery in plants like C. jacea with lesser root trait plasticity after drought, independent of mycorrhizal symbiosis.

Port Accessibility Depends on Cascading Interactions between Fleets, Policies, Infrastructure, and Hydrodynamics - Floor P. Bakker; Solange van der Werff; Fedor Baart; Alex Kirichek; Sander de Jong; Mark van Koningsveld (Journal of Marine Science and Engineering, 2024)
Reducing waiting times is crucial for ports to be efficient and competitive. Important causes of waiting times are cascading interactions between realistic hydrodynamics, accessibility policies, vessel-priority rules, and detailed berth availability. The main challenges are determining the cause of waiting and finding rational solutions to reduce waiting time. In this study, we focus on the role of the design depth of a channel on the waiting times. We quantify the performance of channel depth for a representative fleet rather than the common approach of a single normative design vessel. The study relies on a mesoscale agent-based discrete-event model that can take processed Automatic Identification System and hydrodynamic data as its main input. The presented method’s validity is assessed by hindcasting one year of observed anchorage area laytimes for a liquid bulk terminal in the Port of Rotterdam. The hindcast demonstrates that the method predicts the causes of 73.4% of the non-excessive laytimes of vessels, thereby correctly modelling 60.7% of the vessels-of-call. Following a recent deepening of the access channel, cascading waiting times due to tidal restrictions were found to be limited. Nonetheless, the importance of our approach is demonstrated by testing alternative maintained bed level designs, revealing the method’s potential to support rational decision-making in coastal zones.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Cymbospondylus (Ichthyopterygia) from the Early Triassic of Svalbard and the early evolution of large body size in ichthyosaurs - P. Martin Sander; René Dederichs; Tanja Schaaf; Eva Maria Griebeler (PalZ, 2024)
Ichthyosaurs were a highly successful group of marine reptiles in the Mesozoic. The ichthyosaur radiation is part of the recovery from the Permian-Triassic mass extinction. In the Early Triassic, this group underwent extensive global radiation, filling ecological niches for the first time that were later occupied by various other lineages of marine amniotes. However, the evolution of body size in ichthyosaurs is not fully understood, as most large-bodied taxa originate from the Middle Triassic and later, and are mostly known from only a few specimens. In this study, we describe three articulated posterior dorsal vertebrae (IGPB R660) of the ichthyosaur Cymbospondylus sp. from the latest Olenekian Keyserlingites subrobustus zone of the Vikinghøgda Formation of the Agardhdalen area, eastern Spitsbergen, Svalbard. We numerically estimated the total body length of IGPB R660 from dorsal vertebral centrum length using a comparative dataset of other species of the genus and two different allometric analyses. This approach yields total length estimates of 7.5 m and 9.5 m for the individual, respectively, the highest for any unambiguous Early Triassic ichthyosaur find. Earlier, higher estimates of 11 m were based on taxonomically and stratigraphically inconclusive material but do not appear unreasonable based on evidence provided in this paper. Our study underscores both the rapid ecosystem recovery after a major mass extinction and extremely rapid increases in body size in ichthyosaurs after their adaptation to a secondarily aquatic lifestyle.

Recommendations for the safe use of direct oral anticoagulants in patients with cirrhosis based on a systematic review of pharmacokinetic, pharmacodynamic and safety data - Maaike M. E. Diesveld; Daniëlle W. M. Jacobs- Pijnenburg; Rianne A. Weersink; Ina Barzel; Joost P. H. Drenth; Ton Lisman; Herold J. Metselaar; Margje H. Monster-Simons; Midas B. Mulder; Eline Okel; Katja Taxis; Sander D. Borgsteede (European Journal of Clinical Pharmacology, 2024)

Studying interactions among anthropogenic stressors in freshwater ecosystems: A systematic review of 2396 multiple‐stressor experiments - James A. Orr; Samuel J. Macaulay; Adriana Mordente; Benjamin Burgess; Dania Albini; Julia G. Hunn; Katherin Restrepo‐Sulez; Ramesh Wilson; Anne Schechner; Aoife M. Robertson; Bethany Lee; Blake R. Stuparyk; et al. (Ecology Letters, 2024)
Understanding the interactions among anthropogenic stressors is critical for effective conservation and management of ecosystems. Freshwater scientists have invested considerable resources in conducting factorial experiments to disentangle stressor interactions by testing their individual and combined effects. However, the diversity of stressors and systems studied has hindered previous syntheses of this body of research. To overcome this challenge, we used a novel machine learning framework to identify relevant studies from over 235,000 publications. Our synthesis resulted in a new dataset of 2396 multiple‐stressor experiments in freshwater systems. By summarizing the methods used in these studies, quantifying trends in the popularity of the investigated stressors, and performing co‐occurrence analysis, we produce the most comprehensive overview of this diverse field of research to date. We provide both a taxonomy grouping the 909 investigated stressors into 31 classes and an open‐source and interactive version of the dataset ( https://jamesaorr.shinyapps.io/freshwater‐multiple‐stressors/ ). Inspired by our results, we provide a framework to help clarify whether statistical interactions detected by factorial experiments align with stressor interactions of interest, and we outline general guidelines for the design of multiple‐stressor experiments relevant to any system. We conclude by highlighting the research directions required to better understand freshwater ecosystems facing multiple stressors.

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

Paleoecology and paleobiogeography of the latest Miocene site of Shuitangba, Zhaotong, China - D.F. Su; J. Kelley; L.J. Flynn; X.P. Ji; C.L. Deng; T. Deng; P. Li; Z. Li; W.J. Sanders; T.A. Stidham; F. Sun; X. Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Structural and electro-anatomical characterization of the equine pulmonary veins: implications for atrial fibrillation - S.T. Kjeldsen; S.D. Nissen; A. Saljic; E.M. Hesselkilde; H. Carstensen; S.M. Sattler; T. Jespersen; D. Linz; C. Hopster-Iversen; R. Kutieleh; P. Sanders; R. Buhl (Journal of Veterinary Cardiology, 2024)

Temporal shifts in prokaryotic metabolism in response to organic carbon dynamics in the mesopelagic ocean during an export event in the Southern ocean - Rachel R.-P. Rayne; Sarah L.C. Giering; Manuela Hartmann; Joost Brandsma; Richard D. Sanders; Claire Evans (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

An Organotypic Human Lymph Node Model Reveals the Importance of Fibroblastic Reticular Cells for Dendritic Cell Function - Andrew I. Morrison; Aleksandra M. Mikula; Sander W. Spiekstra; Michael de Kok; Alsya J. Affandi; Henk P. Roest; Luc J. W. van der Laan; Charlotte M. de Winde; Jasper J. Koning; Susan Gibbs; Reina E. Mebius (Tissue Engineering and Regenerative Medicine, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Wave, light, and dissolved oxygen exposures drive novel coastal eelgrass (Zostera pacifica) transplant performance - Rilee D. Sanders; Adam K. Obaza; Benjamin C. Grime; Mathilde Lindhart; Luke P. Miller; Kristen E. Elsmore; Olivia C. Carmack; Tom K. Ford; James J. Leichter (Frontiers in Marine Science, 2024)
The high ecological and economic value of seagrass has been long recognized, with these foundational habitats providing myriad ecosystem services. Yet through cumulative anthropogenic impacts, seagrasses are exhibiting extensive declines globally. A litany of studies and active restoration trials have demonstrated practical methodologies to restore seagrass habitats and effectively return critical habitat functions to degraded coastal zone systems worldwide. Seagrass loss along the U.S. West Coast has precipitated decades of seagrass protection, conservation, and restoration efforts. Yet, mitigation transplanting efforts have prioritized Zostera marina (narrow-leaved eelgrass) in shallow, protected environments, while a dearth of information is available on species inhabiting offshore islands and exposed mainland coasts. In this study, we conducted a novel transplant of Zostera pacifica , a wide-leaved species found in depths of 7 – 20 m along the offshore islands and mainland coast of California. Transplants were conducted at three geographically distinct sites in Santa Monica Bay, coupled with continuous monitoring of biophysical parameters providing insight into physical drivers at transplant and donor sites. Utilizing in situ data, and environmental thresholds adapted from the literature for Z. marina , we performed exposure analyses to evaluate factors influencing Z. pacifica transplant performance. Exceedances of threshold values for environmental parameters, specifically, wave exposure and near-bed flow speeds ( H rms > 0.59 m and U rms > 0.1 m s -1 ), photosynthetically active radiation (< 3 and > 5 mol m -2 day -1 ) and dissolved oxygen (< 3 mg O 2 L -1 ) exposure impacted transplant survivorship. These results suggest Z. pacifica persist in biophysically dynamic conditions and are sensitive to exceedances of thresholds, underlining the importance of pre-transplant site-selection processes to this species. These data represent the first holistic study of Z. pacifica transplanting on an exposed mainland coast, which provides a view into the baseline environmental envelopes within existing Z. pacifica habitat, and further, may serve as a model for investigating scalable open coast seagrass restoration for temperate regions.

Phenotypic screening in Organ-on-a-Chip systems: a 1537 kinase inhibitor library screen on a 3D angiogenesis assay - Camilla Soragni; Karla Queiroz; Chee Ping Ng; Arthur Stok; Thomas Olivier; Dora Tzagkaraki; Jeroen Heijmans; Johnny Suijker; Sander P. M. de Ruiter; Aleksandra Olczyk; Marleen Bokkers; Frederik Schavemaker; et al. (Angiogenesis, 2024)
Modern drug development increasingly requires comprehensive models that can be utilized in the earliest stages of compound and target discovery. Here we report a phenotypic screening exercise in a high-throughput Organ-on-a-Chip setup. We assessed the inhibitory effect of 1537 protein kinase inhibitors in an angiogenesis assay. Over 4000 micro-vessels were grown under perfusion flow in microfluidic chips, exposed to a cocktail of pro-angiogenic factors and subsequently exposed to the respective kinase inhibitors. Efficacy of compounds was evaluated by reduced angiogenic sprouting, whereas reduced integrity of the main micro-vessel was taken as a measure for toxicity. The screen yielded 53 hits with high anti-angiogenicity and low toxicity, of which 44 were previously unassociated with angiogenic pathways. This study demonstrates that Organ-on-a-Chip models can be screened in high numbers to identify novel compounds and targets. This will ultimately reduce bias in early-stage drug development and increases probability to identify first in class compounds and targets for today’s intractable diseases.

How will climate change affect the feeding biology of Collembola? - Shareen K.D. Sanders; Gerard Martínez-De León; Ludovico Formenti; Madhav P. Thakur (Soil Biology and Biochemistry, 2024)

Recent ambient temperature and fine particulate matter (PM2.5) exposure is associated with urinary kidney injury biomarkers in children - Maria D. Politis; Iván Gutiérrez-Avila; Allan Just; María Luisa Pizano-Zárate; Marcela Tamayo-Ortiz; Jason H. Greenberg; Martha M. Téllez-Rojo; Alison P. Sanders; Maria José Rosa (Science of The Total Environment, 2024)

Linking centennial scale anthropogenic changes and sedimentary records as lessons for urban coastal management - Leonardo Amora-Nogueira; Joseph M. Smoak; Rodrigo C. Abuchacra; Carla Carvalho; Fernando C.A. Ribeiro; Kevin C. Martins; Ana L. Fonseca-Oliveira; Manuela Carvalho; Luiza P. Machado; Allana F.F. Souza; André L.C. da Silva; Alex Enrich-Prast; et al. (Science of The Total Environment, 2023)

The long-term dynamics of invasive signal crayfish forcing of fluvial sediment supply via riverbank burrowing - Catherine H. Sanders; Stephen P. Rice; Paul J. Wood; Kate L. Mathers (Geomorphology, 2023)

Suspended particles are hotspots of microbial remineralization in the ocean's twilight zone - V. Hemsley; J. Füssel; M.T. Duret; R.R. Rayne; M.H. Iversen; S.A. Henson; R. Sanders; P. Lam; M. Trimmer (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Normobaric hypoxia shows enhanced FOXO1 signaling in obese mouse gastrocnemius muscle linked to metabolism and muscle structure and neuromuscular innervation - Jingyi Song; Loes P. M. Duivenvoorde; Sander Grefte; Ondrej Kuda; Felipe Martínez-Ramírez; Inge van der Stelt; Dimitra Mastorakou; Evert M. van Schothorst; Jaap Keijer (Pflügers Archiv - European Journal of Physiology, 2023)
Skeletal muscle relies on mitochondria for sustainable ATP production, which may be impacted by reduced oxygen availability (hypoxia). Compared with long-term hypoxia, the mechanistic in vivo response to acute hypoxia remains elusive. Therefore, we aimed to provide an integrated description of the Musculus gastrocnemius response to acute hypoxia. Fasted male C57BL/6JOlaHsd mice, fed a 40en% fat diet for six weeks, were exposed to 12% O 2 normobaric hypoxia or normoxia (20.9% O 2 ) for six hours ( n = 12 per group). Whole-body energy metabolism and the transcriptome response of the M. gastrocnemius were analyzed and confirmed by acylcarnitine determination and Q-PCR. At the whole-body level, six hours of hypoxia reduced energy expenditure, increased blood glucose and tended to decreased the respiratory exchange ratio (RER). Whole-genome transcriptome analysis revealed upregulation of forkhead box-O (FOXO) signalling, including an increased expression of tribbles pseudokinase 3 ( Trib3 ). Trib3 positively correlated with blood glucose levels. Upregulated carnitine palmitoyltransferase 1A negatively correlated with the RER, but the significantly increased in tissue C14-1, C16-0 and C18-1 acylcarnitines supported that β-oxidation was not regulated. The hypoxia-induced FOXO activation could also be connected to altered gene expression related to fiber-type switching, extracellular matrix remodeling, muscle differentiation and neuromuscular junction denervation. Our results suggest that a six-hour exposure of obese mice to 12% O 2 normobaric hypoxia impacts M. gastrocnemius via FOXO1, initiating alterations that may contribute to muscle remodeling of which denervation is novel and warrants further investigation. The findings support an early role of hypoxia in tissue alterations in hypoxia-associated conditions such as aging and obesity.

River bank burrowing is innate in native and invasive signal crayfish (Pacifastacus leniusculus) and is driven by biotic and abiotic cues - C. H. Sanders; S. P. Rice; P. J. Wood; L. K. Albertson (Biological Invasions, 2023)

Corrigendum to “Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum” [Sci. Total Environ. 890 (2023) 164421] - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Johannes Pein; Benjamin Jacob; et al. (Science of The Total Environment, 2023)

Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Dietrich Borchardt; Markus Weitere (Science of The Total Environment, 2023)

Marine nutrient subsidies promote biogeochemical hotspots in undisturbed, highly humic estuaries - Chris D. Evans; Stacey L. Felgate; Steffi Carter; Mark Stinchcombe; Edward Mawji; Andrew P. Rees; Inma Lebron; Richard Sanders; Paul Brickle; Daniel J. Mayor (Limnology and Oceanography, 2023)
The land‐ocean dissolved organic carbon (DOC) flux represents a significant term within the global carbon budget, with peatland‐dominated regions representing the most intense sources of terrestrial DOC export. As the interface between freshwater and marine systems, estuaries have the potential to act as a filter of the land‐ocean carbon flux, removing terrestrially derived DOC, which is present at low concentrations in the oceans, via a combination of physicochemical and biological processes. However, the fate of peat‐derived DOC within estuaries remains poorly quantified, partly due to the complicating influences of heterogeneous soils, land‐use, point sources, and upstream modification of organic matter. To minimize these modifying factors, we studied DOC and inorganic nutrients in four small, peat‐dominated, minimally disturbed, and oligotrophic Falkland Island estuaries. Contrary to expectations, we found limited evidence of physicochemical estuarine DOC removal, and instead observed apparent “hot zones” of biogeochemical activity, where terrestrially‐derived silicate mixed with inorganic nitrogen and phosphorus entering the estuaries from the nutrient‐rich marine ecosystem. In two estuaries, this coincided with apparent in situ DOC production. We suggest that the observed phenomena of marine nutrient subsidy of estuarine productivity, and flexible utilization of multiple nutrients within the oligotrophic system, may once have been widespread in temperate estuaries. However, this function has been lost in many ecosystems due to catchment eutrophication by agricultural and urban development. We conclude that the estuaries of the Falkland Islands provide a valuable pre‐disturbance analogue for natural biogeochemical functioning in temperate estuaries receiving high organic matter inputs.

The characteristics and preservation potential of Hurricane Irma's overwash deposit in southern Florida, USA - Kristen M. Joyse; Nicole S. Khan; Ryan P. Moyer; Kara R. Radabaugh; Isabel Hong; Amanda R. Chappel; Jennifer S. Walker; Christian J. Sanders; Simon E. Engelhart; Robert E. Kopp; Benjamin P. Horton (Marine Geology, 2023)

Multiresidue extraction of current-use pesticides from complex solid matrices using energized dispersive guided extraction with analysis by gas and liquid chromatography tandem mass spectroscopy - Gabrielle P. Black; Emily E. Woodward; Corey J. Sanders; Michael S. Gross; Michelle L. Hladik (Chemosphere, 2023)

Year-round activity levels reveal diurnal foraging constraints in the annual cycle of migratory and non-migratory barnacle geese - Michiel P. Boom; Thomas K. Lameris; Kees H. T. Schreven; Nelleke H. Buitendijk; Sander Moonen; Peter P. de Vries; Elmira Zaynagutdinova; Bart A. Nolet; Henk P. van der Jeugd; Götz Eichhorn (Oecologia, 2023)
Performing migratory journeys comes with energetic costs, which have to be compensated within the annual cycle. An assessment of how and when such compensation occurs is ideally done by comparing full annual cycles of migratory and non-migratory individuals of the same species, which is rarely achieved. We studied free-living migratory and resident barnacle geese belonging to the same flyway (metapopulation), and investigated when differences in foraging activity occur, and when foraging extends beyond available daylight, indicating a diurnal foraging constraint in these usually diurnal animals. We compared foraging activity of migratory (N = 94) and resident (N = 30) geese throughout the annual cycle using GPS-transmitters and 3D-accelerometers, and corroborated this with data on seasonal variation in body condition. Migratory geese were more active than residents during most of the year, amounting to a difference of over 370 h over an entire annual cycle. Activity differences were largest during the periods that comprised preparation for spring and autumn migration. Lengthening days during spring facilitated increased activity, which coincided with an increase in body condition. Both migratory and resident geese were active at night during winter, but migratory geese were also active at night before autumn migration, resulting in a period of night-time activity that was 6 weeks longer than in resident geese. Our results indicate that, at least in geese, seasonal migration requires longer daily activity not only during migration but throughout most of the annual cycle, with migrants being more frequently forced to extend foraging activity into the night.

A walk in the PARC: developing and implementing 21st century chemical risk assessment in Europe - P. Marx-Stoelting; G. Rivière; M. Luijten; K. Aiello-Holden; N. Bandow; K. Baken; A. Cañas; A. Castano; S. Denys; C. Fillol; M. Herzler; I. Iavicoli; et al. (Archives of Toxicology, 2023)
Current approaches for the assessment of environmental and human health risks due to exposure to chemical substances have served their purpose reasonably well. Nevertheless, the systems in place for different uses of chemicals are faced with various challenges, ranging from a growing number of chemicals to changes in the types of chemicals and materials produced. This has triggered global awareness of the need for a paradigm shift, which in turn has led to the publication of new concepts for chemical risk assessment and explorations of how to translate these concepts into pragmatic approaches. As a result, next-generation risk assessment (NGRA) is generally seen as the way forward. However, incorporating new scientific insights and innovative approaches into hazard and exposure assessments in such a way that regulatory needs are adequately met has appeared to be challenging. The European Partnership for the Assessment of Risks from Chemicals (PARC) has been designed to address various challenges associated with innovating chemical risk assessment. Its overall goal is to consolidate and strengthen the European research and innovation capacity for chemical risk assessment to protect human health and the environment. With around 200 participating organisations from all over Europe, including three European agencies, and a total budget of over 400 million euro, PARC is one of the largest projects of its kind. It has a duration of seven years and is coordinated by ANSES, the French Agency for Food, Environmental and Occupational Health & Safety.

Paragenesis of an Ediacaran carbonate-platform phosphorite: Constraints from optical petrography and texture-specific clumped isotope paleothermometry - Cecilia B. Sanders; John C. Eiler; John P. Grotzinger (Sedimentary Geology, 2023)

A cross-validation based approach for estimating specific gravity in elementary-school aged children using a nonlinear model - Stefanie A. Busgang; Syam S. Andra; Paul Curtin; Elena Colicino; Matthew J. Mazzella; Moira Bixby; Alison P. Sanders; John D. Meeker; Marissa Hauptman; Shirisha Yelamanchili; Wanda Phipatanakul; Chris Gennings (Environmental Research, 2023)

Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2023)

Barnacle geese Branta leucopsis breeding on Novaya Zemlya: current distribution and population size estimated from tracking data - Thomas K. Lameris; Olga B. Pokrovskaya; Alexander V. Kondratyev; Yuriy A. Anisimov; Nelleke H. Buitendijk; Petr M. Glazov; Henk P. van der Jeugd; Christian Kampichler; Helmut Kruckenberg; Konstantin E. Litvin; Julia A. Loshchagina; Sander Moonen; et al. (Polar Biology, 2023)
The Russian breeding population of barnacle geese Branta leucopsis has shown a rapid increase in numbers since 1980, which has coincided with a southwest-wards breeding range expansion within the Russian Arctic. Here barnacle geese also started to occupy coastal and marsh land habitats, in which they were not know to nest on their traditional breeding grounds. While these changes have been well documented by studies and observations throughout the new breeding range of barnacle geese, observations are lacking from the traditional breeding grounds on Novaya Zemlya, as this area is remote and difficult to access. This is especially relevant given rapid climate warming in this area, which may impact local distribution and population size. We used GPS-tracking and behavioural biologging data from 46 individual barnacle geese captured on their wintering grounds to locate nest sites in the Russian Arctic and study nesting distribution in 2008–2010 and 2018–2020. Extrapolating from nest counts on Kolguev Island, we estimate the breeding population on Novaya Zemlya in 2018–2020 to range around 75,250 pairs although the confidence interval around this estimate was large. A comparison with the historical size of the barnacle goose population suggests an increase in the breeding population on Novaya Zemlya, corresponding with changes in other areas of the breeding range. Our results show that many barnacle geese on Novaya Zemlya currently nest on lowland tundra on Gusinaya Zemlya Peninsula. This region has been occupied by barnacle geese only since 1990 and appears to be mainly available for nesting in years with early spring. Tracking data are a valuable tool to increase our knowledge of remote locations, but counts of breeding individuals or nests are needed to further corroborate estimates of breeding populations based on tracking data.

Fluoride Exposure and Age of Menarche: Potential Differences Among Adolescent Girls and Women in the United States - Ashley J. Malin; Stefanie A. Busgang; Jaqueline C. Garcia; Sonali Bose; Alison P. Sanders (Exposure and Health, 2022)
Fluoride exposure is associated with later pubertal development and decreased testosterone production in adolescent and adult males. However, its effects on female reproductive health and pubertal development are unclear. Therefore, we examined associations of fluoride exposure with reproductive health outcomes among adolescent girls and women in the United States. Participants were from The National Health and Nutrition Examination Surveys (2013 to 2016), aged 16–19 and identified as female. There were 524 and 460 participants with measures of plasma fluoride and household tap water fluoride respectively, who had at least one reproductive health outcome examined, and complete covariate data. We applied covariate adjusted survey-weighted linear or logistic regression to examine associations of fluoride exposure with age of menarche, menstrual cycle regularity, or serum sex steroid hormone levels. Median interquartile range (IQR) water and plasma fluoride concentrations were 0.48 (0.53) mg/L and 0.34 (0.30) µmol/L respectively. An IQR increase in water fluoride was associated with a 3.3 month earlier first menstrual period ( B = − 0.28, 95%CI − 0.54, − 0.02, p = 0.05). Additionally, we observed a significant interaction between plasma fluoride and race/ethnicity in association with age of menarche ( p = 0.01). Among Non-Hispanic Black adolescents, each IQR increase in plasma fluoride was associated with a 5-month earlier age of menarche ( B = − 0.42, 95%CI − 0.61, − 0.23, p < 0.001). Potential impacts of chronic low-level fluoride exposure on reproductive health outcomes are an important area of study. Current study findings, as well as potential health disparities due to disproportionate fluoride exposure should be examined in prospective studies.

Balancing protein and energy in Nile tilapia feeds: A meta‐analysis - Gauthier D. P. Konnert; Walter J. J. Gerrits; Sander W. S. Gussekloo; Johan W. Schrama (Reviews in Aquaculture, 2022)
Farmed fish are increasingly grown in intensive and semi‐intensive systems where most nutrients are provided by formulated feeds. These are formulated to minimise costs and optimise growth, notably the rate of muscle protein synthesis ( i.e ., fillet). Protein synthesis depends on the availability of amino acids ( i.e ., protein) and energy. Thus, fish feeds are often formulated to provide a balanced ratio of protein to energy (P:E). Above and below the optimal dietary P:E, absorbed protein and energy are expected to be under‐utilised for body protein synthesis, respectively. Estimates of the optimal dietary P:E vary largely for Nile tilapia ( Oreochromis niloticus (L., 1758)). Published values range from 13 to 26 g of dietary protein per MJ of energy. Here, we challenge the idea that growth, protein utilisation efficiency and body composition can all be simultaneously optimised, when Nile tilapia are fed an optimal dietary P:E. Through linear and non‐linear regression meta‐analyses, we quantitatively describe the effects of protein and energy intake on nutrient partitioning, feed efficiency and growth. We find linear relationships between the dietary P:E and protein retention efficiency. The lack of an inflection contradicts the existence of an optimal P:E. Our regressions of protein and energy intake versus protein gain, indicate that protein gain is often simultaneously limited by both protein and energy intake, and may be limited by other factors than protein and energy intake, such as a maximal protein deposition capacity (PD max ). We conclude that there is no physiological basis for an optimal P:E in Nile tilapia feeds.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cancer microenvironment and genomics: evolution in process - Stanley P. Leong; Isaac P. Witz; Orit Sagi-Assif; Sivan Izraely; Jonathan Sleeman; Brian Piening; Bernard A. Fox; Carlo B. Bifulco; Rachel Martini; Lisa Newman; Melissa Davis; Lauren M. Sanders; et al. (Clinical & Experimental Metastasis, 2022)

Optimizing hatchery practices for genetic improvement of marine bivalves - Jennifer C. Nascimento‐Schulze; Tim P. Bean; Ross D. Houston; Eduarda M. Santos; Matthew B. Sanders; Ceri Lewis; Robert P. Ellis (Reviews in Aquaculture, 2021)
Aquaculture currently accounts for approximately half of all seafood produced and is the fastest growing farmed food sector globally. Marine bivalve aquaculture, the farming of oysters, mussels and clams, represents a highly sustainable component of this industry and has major potential for global expansion via increased efficiency, and numbers of, production systems. Artificial spat propagation (i.e. settled juveniles) in hatcheries and selective breeding have the potential to offer rapid and widespread gains for molluscan aquaculture industry. However, bivalves have unique life‐histories, genetic and genomic characteristics, which present significant challenges to achieving such genetic improvement. Selection pressures experienced by bivalve larvae and spat in the wild contribute to drive population structure and animal fitness. Similarly, domestication selection is likely to act on hatchery‐produced spat, the full implications of which have not been fully explored. In this review, we outline the key features of these taxa and production practices applied in bivalve aquaculture, which have the potential to affect the genetic and phenotypic variability of hatchery‐propagated stock. Alongside, we compare artificial and natural processes experienced by bivalves to investigate the possible consequences of hatchery propagation on stock production. In addition, we identify key areas of investigation that need to be prioritized to continue to the advancement of bivalve genetic improvement via selective breeding. The growing accessibility of next‐generation sequencing technology and high‐powered computational capabilities facilitate the implementation of novel genomic tools in breeding programmes of aquatic species. These emerging techniques represent an exciting opportunity for sustainably expanding the bivalve aquaculture sector.

Expanding evaluation of ocean acidification responses in a marine gadid: elevated CO2 impacts development, but not size of larval walleye pollock - Thomas P. Hurst; Louise A. Copeman; Jessica F. Andrade; Michelle A. Stowell; Colleen E. Al-Samarrie; Justin L. Sanders; Michael L. Kent (Marine Biology, 2021)

Pseudocanariomyces americanus, gen. nov., sp. nov., A New Thielavia-Like Species in the Chaetomiaceae: Identification and Management of a Prosthetic Hip Infection - Keenan Ryan; Connie Cañete-Gibas; Carmita Sanders; Nestor Sosa; Nathan P. Wiederhold (Mycopathologia, 2021)

T cell–depleted cultured pediatric thymus tissue as a model for some aspects of human age-related thymus involution - Laura P. Hale; Lynn Cheatham; Andrew N. Macintyre; Bonnie LaFleur; Brittany Sanders; Jesse Troy; Joanne Kurtzberg; Gregory D. Sempowski (GeroScience, 2021)

Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Ruchira Somaweera; Vinay Udyawer; Michael L. Guinea; Daniela M. Ceccarelli; Rohan H. Clarke; Michelle Glover; Mathew Hourston; John Keesing; Arne Redsted Rasmussen; Kate Sanders; Richard Shine; Damian P. Thomson; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.

Clinical Characteristics and Management of 50 Patients with Anti-GAD Ataxia: Gluten-Free Diet Has a Major Impact - M. Hadjivassiliou; P. G. Sarrigiannis; P. D. Shanmugarajah; D. S. Sanders; R. A. Grünewald; P. Zis; N. Hoggard (The Cerebellum, 2021)
The objective of this study is to report the clinical characteristics and treatment of patients with progressive cerebellar ataxia associated with anti-GAD antibodies. We performed a retrospective review of all patients with anti-GAD ataxia managed at the Sheffield Ataxia Centre over the last 25 years. We identified 50 patients (62% females) with anti-GAD ataxia. The prevalence was 2.5% amongst 2000 patients with progressive ataxia of various causes. Mean age at onset was 55 and mean duration 8 years. Gaze-evoked nystagmus was present in 26%, cerebellar dysarthria in 26%, limb ataxia in 44% and gait ataxia in 100%. Nine patients (18%) had severe, 12 (24%) moderate and 29 (58%) mild ataxia. Ninety percent of patients had a history of additional autoimmune diseases. Family history of autoimmune diseases was seen in 52%. Baseline MR spectroscopy of the vermis was abnormal at presentation in 72%. Thirty-five patients (70%) had serological evidence of gluten sensitivity. All 35 went on gluten-free diet (GFD). Eighteen (51%) improved, 13 (37%) stabilised, 3 have started the GFD too recently to draw conclusions and one deteriorated. Mycophenolate was used in 16 patients, 7 (44%) improved, 2 stabilised, 6 have started the medication too recently to draw conclusions and one did not tolerate the drug. There is considerable overlap between anti-GAD ataxia and gluten ataxia. For those patients with both, strict GFD alone can be an effective treatment. Patients with anti-GAD ataxia and no gluten sensitivity respond well to immunosuppression.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

An Integrative Model of Carbon and Nitrogen Metabolism in a Common Deep-Sea Sponge (Geodia barretti) - Anna de Kluijver; Martijn C. Bart; Dick van Oevelen; Jasper M. de Goeij; Sally P. Leys; Sandra R. Maier; Manuel Maldonado; Karline Soetaert; Sander Verbiest; Jack J. Middelburg (Frontiers in Marine Science, 2021)
Deep-sea sponges and their microbial symbionts transform various forms of carbon (C) and nitrogen (N) via several metabolic pathways, which, for a large part, are poorly quantified. Previous flux studies on the common deep-sea sponge Geodia barretti consistently revealed net consumption of dissolved organic carbon (DOC) and oxygen (O 2 ) and net release of nitrate ( NO 3 - ). Here we present a biogeochemical metabolic network model that, for the first time, quantifies C and N fluxes within the sponge holobiont in a consistent manner, including many poorly constrained metabolic conversions. Using two datasets covering a range of individual G. barretti sizes (10–3,500 ml), we found that the variability in metabolic rates partially resulted from body size as O 2 uptake allometrically scales with sponge volume. Our model analysis confirmed that dissolved organic matter (DOM), with an estimated C:N ratio of 7.7 ± 1.4, is the main energy source of G. barretti. DOM is primarily used for aerobic respiration, then for dissimilatory NO 3 - reduction to ammonium ( NH 4 + ) (DNRA), and, lastly, for denitrification. Dissolved organic carbon (DOC) production efficiencies (production/assimilation) were estimated as 24 ± 8% (larger individuals) and 31 ± 9% (smaller individuals), so most DOC was respired to carbon dioxide (CO 2 ), which was released in a net ratio of 0.77–0.81 to O 2 consumption. Internally produced NH 4 + from cellular excretion and DNRA fueled nitrification. Nitrification-associated chemoautotrophic production contributed 5.1–6.7 ± 3.0% to total sponge production. While overall metabolic patterns were rather independent of sponge size, (volume-)specific rates were lower in larger sponges compared to smaller individuals. Specific biomass production rates were 0.16% day –1 in smaller compared to 0.067% day –1 in larger G. barretti as expected for slow-growing deep-sea organisms. Collectively, our approach shows that metabolic modeling of hard-to-reach, deep-water sponges can be used to predict community-based biogeochemical fluxes and sponge production that will facilitate further investigations on the functional integration and the ecological significance of sponge aggregations in deep-sea ecosystems.

Urinary MicroRNAs in Environmental Health: Biomarkers of Emergent Kidney Injury and Disease - Alison H. Harrill; Alison P. Sanders (Current Environmental Health Reports, 2020)

Correction to: Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2020)
Due to an error during the editorial phase, a correction regarding Fig. 2 is added to the original article: “Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis”. Please see below correct Fig. 2.

Divergent carbon cycle response of forest and grass‐dominated northern temperate ecosystems to record winter warming - Rebecca Sanders‐DeMott; Andrew P. Ouimette; Lucie C. Lepine; Sean Z. Fogarty; Elizabeth A. Burakowski; Alexandra R. Contosta; Scott V. Ollinger (Global Change Biology, 2020)
Northern temperate ecosystems are experiencing warmer and more variable winters, trends that are expected to continue into the foreseeable future. Despite this, most studies have focused on climate change impacts during the growing season, particularly when comparing responses across different vegetation cover types. Here we examined how a perennial grassland and adjacent mixed forest ecosystem in New Hampshire, United States, responded to a period of highly variable winters from 2014 through 2017 that included the warmest winter on record to date. In the grassland, record‐breaking temperatures in the winter of 2015/2016 led to a February onset of plant growth and the ecosystem became a sustained carbon sink well before winter ended, taking up roughly 90 g/m 2 more carbon during the winter to spring transition than in other recorded years. The forest was an unusually large carbon source during the same period. While forest photosynthesis was restricted by leaf‐out phenology, warm winter temperatures caused large pulses of ecosystem respiration that released nearly 230 g C/m 2 from February through April, more than double the carbon losses during that period in cooler years. These findings suggest that, as winters continue to warm, increases in ecosystem respiration outside the growing season could outpace increases in carbon uptake during a longer growing season, particularly in forests that depend on leaf‐out timing to initiate carbon uptake. In ecosystems with a perennial leaf habit, warming winter temperatures are more likely to increase ecosystem carbon uptake through extension of the active growing season. Our results highlight the importance of understanding relationships among antecedent winter conditions and carbon exchange across land‐cover types to understand how landscape carbon exchange will change under projected climate warming.

Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij-van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2019)
Cognition in absence epilepsy (AE) is generally considered undisturbed. However, reports on cognitive deficits in AE in recent years have suggested otherwise. This review systematically assesses current literature on cognitive performance in children with AE. A systematic literature search was performed in Pubmed, Embase, Cochrane and Web of Science. All studies reporting on cognitive performance in children with AE were considered. In total 33 studies were eligible for inclusion. Neuropsychological tests were classified into the following domains: intelligence; executive function; attention; language; motor & sensory-perceptual examinations; visuoperceptual/visuospatial/visuoconstructional function; memory and learning; achievement. Random-effect meta-analyses were conducted by estimating the pooled mean and/or pooling the mean difference in case-control studies. Full-scale IQ in children with AE was estimated at 96.78 (95%CI:94.46–99.10) across all available studies and in case-control studies IQ was on average 8.03 (95%CI:-10.45- -5.61) lower. Verbal IQ was estimated at 97.98 (95%CI:95.80–100.16) for all studies and 9.01 (95%CI:12.11- -5.90) points lower in case-control studies. Performance IQ was estimated at 97.23 (93.24–101.22) for all available studies and 5.32 (95%CI:-8.27–2.36) points lower in case-control studies. Lower performance was most often reported in executive function (cognitive flexibility, planning, and verbal fluency) and attention (sustained, selective and divided attention). Reports on school difficulties, neurodevelopmental problems, and attentional problems were high. In conclusion, in contrast to common beliefs, lower than average neurocognitive performance was noted in multiple cognitive domains, which may influence academic and psychosocial development.

Fossil burrow assemblage, not mangrove roots: reinterpretation of the main whale-bearing layer in the late Eocene of Wadi Al-Hitan, Egypt - Carole T. Gee; P. Martin Sander; Shanan E. Peters; Mohamed Talaat El-Hennawy; Mohammed Sameh M. Antar; Iyad S. Zalmout; Philip D. Gingerich (Palaeobiodiversity and Palaeoenvironments, 2019)

A large temnospondyl humerus from the Rhaetian (Late Triassic) of Bonenburg (Westphalia, Germany) and its implications for temnospondyl extinction - Dorota Konietzko-Meier; Jennifer D. Werner; Tanja Wintrich; P. Martin Sander (Journal of Iberian Geology, 2019)

The uniquely diverse taphonomy of the marine reptile skeletons (Sauropterygia) from the Lower Muschelkalk (Anisian) of Winterswijk, The Netherlands - Jelle Heijne; Nicole Klein; P. Martin Sander (PalZ, 2019)

Deriving Environmental Life Cycle Inventory Factors for Land Application of Garden Waste Products Under Northern European Conditions - Martin P. Nielsen; Hiroko Yoshida; Shimelis G. Raji; Charlotte Scheutz; Lars S. Jensen; Thomas H. Christensen; Sander Bruun (Environmental Modeling & Assessment, 2019)

Toxic Metals and Chronic Kidney Disease: a Systematic Review of Recent Literature - Emily C. Moody; Steven G. Coca; Alison P. Sanders (Current Environmental Health Reports, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

The first record of Tyrannoneustes (Thalattosuchia: Metriorhynchidae): a complete skull from the Callovian (late Middle Jurassic) of Germany - Katja Waskow; Detlef Grzegorczyk; P. Martin Sander (PalZ, 2018)

Infestation of shore crab gills by a free-living mussel species - Rowan Poulter; P. Graham Oliver; Chris Hauton; Trystan Sanders; Benjamin J. Ciotti (Marine Biodiversity, 2018)

Variability of growth pattern observed in Metoposaurus krasiejowensis humeri and its biological meaning - Elżbieta M. Teschner; P. Martin Sander; Dorota Konietzko-Meier (Journal of Iberian Geology, 2018)

Avoiding timescale bias in assessments of coastal wetland vertical change - Joshua L. Breithaupt; Joseph M. Smoak; Robert H. Byrne; Matthew N. Waters; Ryan P. Moyer; Christian J. Sanders (Limnology and Oceanography, 2018)
There is concern that accelerating sea‐level rise will exceed the vertical growth capacity of coastal‐wetland substrates in many regions by the end of this century. Vertical vulnerability estimates rely on measurements of accretion and/or surface‐elevation‐change derived from soil cores and/or surface elevation tables (SETs). To date there has not been a broad examination of whether the multiple timescales represented by the processes of accretion and elevation change are equally well‐suited for quantifying the trajectories of wetland vertical change in coming decades and centuries. To examine the potential for timescale bias in assessments of vertical change, we compared rates of accretion and surface elevation change using data derived from a review of the literature. In the first approach, average rates of elevation change were compared with timescale‐averaged accretion rates from six regions around the world where sub‐decadal, decadal, centennial, and millennial timescales were represented. Second, to isolate spatial variability, temporal comparisons were made for regionally unique environmental categories within each region. Last, comparisons were made of records from sites where SET‐MH stations and radiometric measurements were co‐located in close proximity. We find that rates vary significantly as a function of measurement timescale and that the pattern and magnitude of variation between timescales are location‐specific. Failure to identify and account for temporal variability in rates will produce biased assessments of the vertical change capacity of coastal wetlands. Robust vulnerability assessments should combine accretion rates from multiple timescales with the longest available SET record to provide long‐term context for ongoing monitoring observations and projections.

In vivo visualization of the locus coeruleus in humans: quantifying the test–retest reliability - Klodiana-Daphne Tona; Max C. Keuken; Mischa de Rover; Egbert Lakke; Birte U. Forstmann; Sander Nieuwenhuis; Matthias J. P. van Osch (Brain Structure and Function, 2017)

Rainbow trout ( Oncorhynchus mykiss ) immune response towards a recombinant vaccine targeting the parasitic ciliate Ichthyophthirius multifiliis - L von Gersdorff Jørgensen; P W Kania; K J Rasmussen; A H Mattsson; J Schmidt; A Al‐Jubury; A Sander; A Salanti; K Buchmann (Journal of Fish Diseases, 2017)
The protective effect in rainbow trout ( Oncorhynchus mykiss ) of an experimental subunit vaccine targeting antigens in the parasite Ichthyophthirius multifiliis has been evaluated and compared to effects elicited by a classical parasite homogenate vaccine. Three recombinant parasite proteins (two produced in E. coli and one in insect cells) were combined and injected i.p., and subsequently, protection and antibody responses were analysed. Both the experimental and the benchmark vaccine induced partial but significant protection against I. multifiliis when compared to control fish. Specific antibody responses of vaccinated trout (subunit vaccine) were raised against one neurohypophysial n‐terminal domain protein #10 of three recombinant proteins, whereas the benchmark vaccine group showed specific antibody production against all three recombinant proteins. The immunogenic parasite protein #10 may be a potential vaccine candidate supplementing the protective I‐antigen in future vaccine trials.

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Precise oligonucleotide-directed mutagenesis of the Chlamydomonas reinhardtii genome - Wen-Zhi Jiang; Sarah Dumm; Mark E. Knuth; Steven L. Sanders; Donald P. Weeks (Plant Cell Reports, 2017)

Cost-effectiveness analysis of universal screening for carbapenemase-producing Enterobacteriaceae in hospital inpatients - L. Lapointe-Shaw; T. Voruganti; P. Kohler; H.-H. Thein; B. Sander; A. McGeer (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Interspecific hybridization causes long‐term phylogenetic discordance between nuclear and mitochondrial genomes in freshwater fishes - Graham P. Wallis; Sophia R. Cameron‐Christie; Hannah L. Kennedy; Gemma Palmer; Tessa R. Sanders; David J. Winter (Molecular Ecology, 2017)
Classification, phylogeography and the testing of evolutionary hypotheses rely on correct estimation of species phylogeny. Early molecular phylogenies often relied on mt DNA alone, which acts as a single linkage group with one history. Over the last decade, the use of multiple nuclear sequences has often revealed conflict among gene trees. This observation can be attributed to hybridization, lineage sorting, paralogy or selection. Here, we use 54 groups of fishes from 48 studies to estimate the degree of concordance between mitochondrial and nuclear gene trees in two ecological grades of fishes: marine and freshwater. We test the hypothesis that freshwater fish phylogenies should, on average, show more discordance because of their higher propensity for hybridization in the past. In keeping with this idea, concordance between mitochondrial and nuclear gene trees (as measured by proportion of components shared) is on average 50% higher in marine fishes. We discuss why this difference almost certainly results from introgression caused by greater historical hybridization among lineages in freshwater groups, and further emphasize the need to use multiple nuclear genes, and identify conflict among them, in estimation of species phylogeny.

M ycobacterium ulcerans toxin, mycolactone may enhance host‐seeking and oviposition behaviour by A edes aegypti ( L .) ( D iptera: C ulicidae) - M. L. Sanders; H. R. Jordan; C. Serewis‐Pond; L. Zheng; M. E. Benbow; P. L. Small; J. K. Tomberlin (Environmental Microbiology, 2017)
Summary The ecological functions of many toxins continue to remain unknown for those produced by environmental pathogens. Mycobacterium ulcerans , the causative agent of the neglected tropical disease, Buruli ulcer, produces a cytotoxic macrolide, mycolactone, whose function(s) in the environment remains elusive. Through a series of dual‐choice behaviour assays, they show that mycolactone may be an interkingdom cue for the yellow fever mosquito, Aedes aegypti , seeking blood‐meals as well as oviposition sites. Results provide novel insight into the evolution between bacteria and potential vectors. While further studies are needed to determine if mycolactone is an actual signal rather than simply a cue, this discovery could serve as a model for determining roles for toxins produced by other environmental pathogens and provide opportunities for developing novel strategies for disease prevention. The relationship between M. ulcerans , mycolactone, and Ae. aegypti further suggests there could be an amplification effect for the spread of pathogens responsible for other diseases, such as yellow fever and dengue.

Leeches as a source of mammalian viral DNA and RNA—a study in medicinal leeches - Marie-Louise Kampmann; Ida Bærholm Schnell; Randi Holm Jensen; Jan Axtner; Adam F. Sander; Anders J. Hansen; Mads F. Bertelsen; Alex D. Greenwood; M. Thomas P. Gilbert; Andreas Wilting (European Journal of Wildlife Research, 2017)

The dentition of a well-preserved specimen of Camarasaurus sp.: implications for function, tooth replacement, soft part reconstruction, and food intake - Kayleigh Wiersma; P. Martin Sander (PalZ, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Gut microbiota of dung beetles correspond to dietary specializations of adults and larvae - Shantanu P. Shukla; Jon G. Sanders; Marcus J. Byrne; Naomi E. Pierce (Molecular Ecology, 2016)
Vertebrate dung is central to the dung beetle life cycle, constituting food for adults and a protective and nutritive refuge for their offspring. Adult dung beetles have soft mandibles and feed primarily on nutritionally rich dung particles, while larvae have sclerotized mandibles and consume coarser dung particles with a higher C/N ratio. Here, using the dung beetles Euoniticellus intermedius and E. triangulatus , we show that these morphological adaptations in mandibular structure are also correlated with differences in basic gut structure and gut bacterial communities between dung beetle life stages. Metagenome functional predictions based on 16S rDNA characterization further indicated that larval gut communities are enriched in genes involved in cellulose degradation and nitrogen fixation compared to adult guts. Larval gut communities are more similar to female gut communities than they are to those of males, and bacteria present in maternally provisioned brood balls and maternal ‘gifts’ (secretions deposited in the brood ball along with the egg) are also more similar to larval gut communities than to those of males. Maternal secretions and maternally provisioned brood balls, as well as dung, were important factors shaping the larval gut community. Differences between gut microbiota in the adults and larvae are likely to contribute to differences in nutrient assimilation from ingested dung at different life history stages.

Reducing emissions from agriculture to meet the 2 °C target - Eva Wollenberg; Meryl Richards; Pete Smith; Petr Havlík; Michael Obersteiner; Francesco N. Tubiello; Martin Herold; Pierre Gerber; Sarah Carter; Andrew Reisinger; Detlef P. van Vuuren; Amy Dickie; et al. (Global Change Biology, 2016)
More than 100 countries pledged to reduce agricultural greenhouse gas ( GHG ) emissions in the 2015 Paris Agreement of the United Nations Framework Convention on Climate Change. Yet technical information about how much mitigation is needed in the sector vs. how much is feasible remains poor. We identify a preliminary global target for reducing emissions from agriculture of ~1 Gt CO 2 e yr −1 by 2030 to limit warming in 2100 to 2 °C above pre‐industrial levels. Yet plausible agricultural development pathways with mitigation cobenefits deliver only 21–40% of needed mitigation. The target indicates that more transformative technical and policy options will be needed, such as methane inhibitors and finance for new practices. A more comprehensive target for the 2 °C limit should be developed to include soil carbon and agriculture‐related mitigation options. Excluding agricultural emissions from mitigation targets and plans will increase the cost of mitigation in other sectors or reduce the feasibility of meeting the 2 °C limit.

Neural substrates of successful working memory and long-term memory formation in a relational spatial memory task - Heiko C. Bergmann; Sander M. Daselaar; Guillén Fernández; Roy P. C. Kessels (Cognitive Processing, 2016)

Toward a Quality-Controlled and Accessible Pitzer Model for Seawater and Related Systems - David R. Turner; Eric P. Achterberg; Chen-Tung A. Chen; Simon L. Clegg; Vanessa Hatje; Maria T. Maldonado; Sylvia G. Sander; Constant M. G. van den Berg; Mona Wells (Frontiers in Marine Science, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Ustilago echinata: Infection in a Mixed Martial Artist Following an Open Fracture - Ethan Stewart; Sarah Waldman; Deanna A. Sutton; Carmita Sanders; Jonathan Lindner; Hongxin Fan; Nathan P. Wiederhold; George R. Thompson (Mycopathologia, 2016)

Improved Geometry of Decellularized Tissue Engineered Heart Valves to Prevent Leaflet Retraction - Bart Sanders; Sandra Loerakker; Emanuela S. Fioretta; Dave J.P. Bax; Anita Driessen-Mol; Simon P. Hoerstrup; Frank P. T. Baaijens (Annals of Biomedical Engineering, 2016)

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction - Alexandre Luz de Castro; Rafael Oliveira Fernandes; Vanessa D. Ortiz; Cristina Campos; Jéssica H. P. Bonetto; Tânia R. G. Fernandes; Adriana Conzatti; Rafaela Siqueira; Angela Vicente Tavares; Paulo Cavalheiro Schenkel; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Apoptosis, 2016)

Long-Term Emission Factors for Land Application of Treated Organic Municipal Waste - Hiroko Yoshida; Martin P. Nielsen; Charlotte Scheutz; Lars S. Jensen; Sander Bruun; Thomas H. Christensen (Environmental Modeling & Assessment, 2016)

Family history of hematologic malignancies and risk of multiple myeloma: differences by race and clinical features - MaryAnn E. VanValkenburg; Gwendolyn I. Pruitt; Ilene K. Brill; Luciano Costa; Maryam Ehtsham; Ian T. Justement; Racquel D. Innis-Shelton; Donna Salzman; E. Shyam P. Reddy; Kelly N. Godby; Fady M. Mikhail; Andrew J. Carroll; et al. (Cancer Causes & Control, 2016)

Postcranial material of Nothosaurus marchicus from the Lower Muschelkalk (Anisian) of Winterswijk, The Netherlands, with remarks on swimming styles and taphonomy - Nicole Klein; Dennis F. A. E. Voeten; Jos Lankamp; Remco Bleeker; Oliver J. Sichelschmidt; Marco Liebrand; Dennis C. Nieweg; P. Martin Sander (PalZ, 2015)

Skeletal material from larger Eusauropterygia (Reptilia: Eosauropterygia) with nothosaurian and cymatosaurian affinities from the Lower Muschelkalk of Winterswijk, The Netherlands - Dennis F. A. E. Voeten; P. Martin Sander; Nicole Klein (PalZ, 2015)

Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms - Robert W. Sanders; Sandra L. Cooke; Janet M. Fischer; Samuel B. Fey; Adam W. Heinze; Wade H. Jeffrey; Amy L. Macaluso; Robert E. Moeller; Donald P. Morris; Patrick J. Neale; Mark H. Olson; J. Dean Pakulski; et al. (Limnology and Oceanography, 2015)
Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA 320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1 , 3.0 mg L −1 , and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA 320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA 320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA 320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.

Beta receptor-mediated modulation of the oddball P3 but not error-related ERP components in humans - Mischa de Rover; Stephen B. R. E. Brown; Guido P. Band; Erik J. Giltay; Martijn S. van Noorden; Nic J. A. van der Wee; Sander Nieuwenhuis (Psychopharmacology, 2015)

Perinatal and Childhood Exposure to Cadmium, Manganese, and Metal Mixtures and Effects on Cognition and Behavior: A Review of Recent Literature - Alison P. Sanders; Birgit Claus Henn; Robert O. Wright (Current Environmental Health Reports, 2015)

The zebrafish, Danio rerio, as a model for Toxoplasma gondii : an initial description of infection in fish - J L Sanders; Y Zhou; H M Moulton; Z X Moulton; R McLeod; J P Dubey; L M Weiss; M L Kent (Journal of Fish Diseases, 2015)

Influence of Pathogenic Mutations on the Energetics of Translocon-Mediated Bilayer Integration of Transmembrane Helices - Jonathan P. Schlebach; Charles R. Sanders (The Journal of Membrane Biology, 2015)

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

Bacteraemic and non-bacteraemic/urinary antigen-positive pneumococcal community-acquired pneumonia compared - S. P. van Mens; A. M. M. van Deursen; S. C. de Greeff; H. E. de Melker; L. M. Schouls; A. van der Ende; M. J. M. Bonten; E. A. M. Sanders; B. J. M. Vlaminckx (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A framework with an integrated computer support tool to assess regional biomass delivery chains - B. S. Elbersen; E. Annevelink; J. Roos Klein-Lankhorst; J. P. Lesschen; I. Staritsky; J. W. A. Langeveld; H. W. Elbersen; J. P. M. Sanders (Regional Environmental Change, 2014)

ANGPTL4 is produced by entero-endocrine cells in the human intestinal tract - Sheril Alex; Laeticia Lichtenstein; Wieneke Dijk; Ronald P. Mensink; Nguan Soon Tan; Sander Kersten (Histochemistry and Cell Biology, 2014)

Postcranial morphology of a basal Pistosauroidea (Sauropterygia) from the Lower Muschelkalk of Winterswijk, The Netherlands - P. Martin Sander; Nicole Klein; Paul C. H. Albers; Constanze Bickelmann; Herman Winkelhorst (PalZ, 2014)

Tobacco smoking, NBS1 polymorphisms, and survival in lung and upper aerodigestive tract cancers with semi-Bayes adjustment for hazard ratio variation - Tingting Yang; Po-Yin Chang; Sungshim Lani Park; Delara Bastani; Shen-Chih Chang; Hal Morgenstern; Donald P. Tashkin; Jenny T. Mao; Jeanette C. Papp; Jian-Yu Rao; Wendy Cozen; Thomas M. Mack; et al. (Cancer Causes & Control, 2014)

Rates and Probable Causes of Freshwater Tidal Marsh Failure, Potomac River Estuary, Northern Virginia, USA - Ronald J. Litwin; Joseph P. Smoot; Milan J. Pavich; Erik Oberg; Brent Steury; Ben Helwig; Helaine W. Markewich; Vincent L. Santucci; Geoffrey Sanders (Wetlands, 2013)

The vestibular system does not modulate fusimotor drive to muscle spindles in contracting leg muscles of seated subjects - L. R. Bent; M. Sander; P. S. Bolton; V. G. Macefield (Experimental Brain Research, 2013)

Stochastic and deterministic drivers of spatial and temporal turnover in breeding bird communities - James C. Stegen; Amy L. Freestone; Thomas O. Crist; Marti J. Anderson; Jonathan M. Chase; Liza S. Comita; Howard V. Cornell; Kendi F. Davies; Susan P. Harrison; Allen H. Hurlbert; Brian D. Inouye; Nathan J. B. Kraft; et al. (Global Ecology and Biogeography, 2013)
Aim A long‐standing challenge in ecology is to identify the suite of factors that lead to turnover in species composition in both space and time. These factors might be stochastic (e.g. sampling and priority effects) or deterministic (e.g. competition and environmental filtering). While numerous studies have examined the relationship between turnover and individual drivers of interest (e.g. primary productivity, habitat heterogeneity, or regional – ‘gamma’ – diversity), few studies have disentangled the simultaneous influences of multiple stochastic and deterministic processes on both temporal and spatial turnover. If turnover is governed primarily by stochastic sampling processes, removing the sampling effects of gamma diversity should result in non‐significant relationships between turnover and environmental variables. Conversely, if deterministic processes govern turnover patterns, removing sampling effects will have little influence on turnover gradients. Here, we test these predictions. Location The United States. Methods Continental‐scale, multidecadal data were used to quantify spatial and temporal turnover in avian community composition within 295 survey routes. A series of regression and structural equation models were coupled with a null model to construct statistical models describing turnover patterns. Results Examining explanatory variables alone or in combination showed that spatial and temporal turnover increased together, decreased with primary productivity and increased with habitat heterogeneity. The relationships between turnover and all variables became weaker when sampling effects were removed, but relationships with primary productivity and habitat heterogeneity remained relatively strong. In addition, spatial turnover increased strongly with spatial gamma diversity after sampling effects were removed. Main conclusions Our results show that spatial and temporal turnover are related to each other through a stochastic sampling process, but that each type of turnover is further influenced by deterministic processes. The relative influence of deterministic processes appears, however, to decrease with primary productivity and increase with habitat heterogeneity across an east–west longitudinal gradient in North America.

Rapid identification of bacteria in positive blood culture by matrix-assisted laser desorption ionization time-of-flight mass spectrometry - V. Schmidt; A. Jarosch; P. März; C. Sander; V. Vacata; W. Kalka-Moll (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Magnetoencephalographic and Magnetic Resonance Spectroscopy Evidence of Regional Functional Abnormality in Mesial Temporal Lobe Epilepsy - Jerry J. Shih; Michael P. Weisend; John A. Sanders; Roland R. Lee (Brain Topography, 2011)

Holocene flooding history of the Lower Tagus Valley (Portugal) - Geert‐Jan Vis; Sjoerd J. P. Bohncke; Heike Schneider; Cornelis Kasse; Sander Coenraads‐Nederveen; Koen Zuurbier; Jouke Rozema (Journal of Quaternary Science, 2010)
The present paper aims to reconstruct the Lower Tagus Valley flooding history for the last ca. 6500 a, to explore the suitability of pollen‐based local vegetation development in supporting the reconstruction of flooding history, and to explain fluvial activity changes in terms of allogenic (climate, human impact) and autogenic (system intrinsic) processes. The flooding history has been determined by cored sedimentary records located ∼18 km apart in distal, low‐energy backswamps on both sides of the Tagus channel. In these low‐energy backswamps, fine‐grained sediment layers deposited from suspended load of overbank flood water reflect periods with multiple overbank floods. By means of a multi‐proxy approach (sedimentology, magnetic susceptibility, grain size, loss‐on‐ignition, carbonate content and pollen), sedimentary and environmental changes were identified. At both sites, synchronous lithological intervals accumulated, suggesting a common origin for the changes in fluvial activity since ca. 6500 cal. a BP. Based on lithological changes, three phases of high fluvial activity (6500–5500, 4900–3500 and 1000–0 cal. a BP) and two phases of low fluvial activity (5500–4900 and 3500–1000 cal. a BP) were identified. Two periods with dominant allogenic controls on fluvial activity in the Lower Tagus Valley were identified: relative sea level (6500–5500 cal. a BP) and human impact (1000–0 cal. a BP). During the intermediate period, changes in fluvial activity may have been caused by climate (5500–1000 cal. BP), but unambiguous correlations are difficult to make. This is due to the way allogenic controls are translated through the fluvial system, the geomorphological differences between upstream and downstream studies and autogenic processes. The comparison of local vegetation development and flooding phases as reconstructed using sedimentology shows a limited added value of using local palynology as a proxy for fluvial activity. Copyright © 2010 John Wiley & Sons, Ltd.

Association Study of TRPC4 as a Candidate Gene for Generalized Epilepsy with Photosensitivity - Sarah von Spiczak; Hiltrud Muhle; Ingo Helbig; Carolien G. F. de Kovel; Jochen Hampe; Verena Gaus; Bobby P. C. Koeleman; Dick Lindhout; Stefan Schreiber; Thomas Sander; Ulrich Stephani (NeuroMolecular Medicine, 2010)

Remineralization of upper ocean particles: Implications for iron biogeochemistry - P. W. Boyd; E. Ibisanmi; S. G. Sander; K. A. Hunter; G. A. Jackson (Limnology and Oceanography, 2010)
The role of heterotrophic bacteria in iron recycling, the influence of complexation on iron remineralization, and iron mobilization rates from lithogenic vs. biogenic particulate iron (PFe) were examined using field experiments and modeling simulations. During summer, we measured the mobilization rate of algal iron by heterotrophic bacteria in the mixed layer at a polar and a subpolar site south of Australia, and conducted shipboard incubations to track the release of dissolved iron (DFe) and iron‐binding ligands from subsurface settling particles sampled from 120‐m depth. Bacteria mobilized > 25% PFe d −1 in surface waters relative to mobilization at depth ( −1 ). Our incubations provide the first evidence of the concurrent release of weak iron‐binding ligands and DFe from sinking particles. Simulated profiles of PFe remineralization, based on proxies, point to greater dissolution from biogenic PFe than from lithogenic PFe. Together our findings point to different biogeochemical functions for lithogenic vs. biogenic PFe: biogenic PFe is probably the main source of both DFe and ligands, whereas lithogenic PFe may contribute most to DFe scavenging and ballasting of biogenic PFe. The relative proportions of lithogenic vs. biogenic PFe flux vary regionally and set the contribution of scavenging and ballasting vs. dissolution and ligand release, and hence the fate of iron in the water column.

Electron Partitioning During Light- and Nutrient-Powered Hydrogen Production by Rhodobacter sphaeroides - Luftu Safak Yilmaz; Wayne S. Kontur; Alison P. Sanders; Ugur Sohmen; Timothy J. Donohue; Daniel R. Noguera (BioEnergy Research, 2010)

Validation of a liquid chromatography-tandem mass spectrometry screening method to monitor 58 antibiotics in milk: a qualitative approach - M. Gaugain-Juhel; B. Delépine; S. Gautier; M.P. Fourmond; V. Gaudin; D. Hurtaud-Pessel; E. Verdon; P. Sanders (Food Additives & Contaminants: Part A, 2009)

Effects of temperature on disease progression and swimming stamina in Ichthyophonus ‐infected rainbow trout, Oncorhynchus mykiss (Walbaum) - R Kocan; P Hershberger; G Sanders; J Winton (Journal of Fish Diseases, 2009)
Rainbow trout, Oncorhynchus mykiss , were infected with Ichthyophonus sp. and held at 10 °C, 15 °C and 20 °C for 28 days to monitor mortality and disease progression. Infected fish demonstrated more rapid onset of disease, higher parasite load, more severe host tissue reaction and reduced mean‐day‐to‐death at higher temperature. In a second experiment, Ichthyophonus ‐infected fish were reared at 15 °C for 16 weeks then subjected to forced swimming at 10 °C, 15 °C and 20 °C. Stamina improved significantly with increased temperature in uninfected fish; however, this was not observed for infected fish. The difference in performance between infected and uninfected fish became significant at 15 °C ( P = 0.02) and highly significant at 20 °C ( P = 0.005). These results have implications for changes in the ecology of fish diseases in the face of global warming and demonstrate the effects of higher temperature on the progression and severity of ichthyophoniasis as well as on swimming stamina, a critical fitness trait of salmonids. This study helps explain field observations showing the recent emergence of clinical ichthyophoniasis in Yukon River Chinook salmon later in their spawning migration when water temperatures were high, as well as the apparent failure of a substantial percentage of infected fish to successfully reach their natal spawning areas.

Temperature-mediated coexistence in temperate forest ant communities - J.-P. Lessard; R. R. Dunn; N. J. Sanders (Insectes Sociaux, 2009)

Comparative study of three screening tests, two microbiological tube tests, and a multi-sulphonamide ELISA kit for the detection of antimicrobial and sulphonamide residues in eggs - V. Gaudin; C. Hedou; A. Rault; P. Sanders; E. Verdon (Food Additives & Contaminants: Part A, 2009)

Swimming obstructed by dead-water - Sander P. M. Ganzevles; Fons S. W. van Nuland; Leo R. M. Maas; Huub M. Toussaint (The Science of Nature, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Emotional exhaustion and mental health problems among employees doing “people work”: the impact of job demands, job resources and family-to-work conflict - Geertje van Daalen; Tineke M. Willemsen; Karin Sanders; Marc J. P. M. van Veldhoven (International Archives of Occupational and Environmental Health, 2009)

The organophosphorous pesticide, fenitrothion, acts as an anti-androgen and alters reproductive behavior of the male three-spined stickleback, Gasterosteus aculeatus - Marion Sebire; Alexander P. Scott; Charles R. Tyler; James Cresswell; Dave J. Hodgson; Steve Morris; Matthew B. Sanders; Paul D. Stebbing; Ioanna Katsiadaki (Ecotoxicology, 2009)

An Outwardly Rectifying and Deactivating Chloride Channel Expressed by Interstitial Cells of Cajal from the Murine Small Intestine - Sean P. Parsons; Kenton M. Sanders (The Journal of Membrane Biology, 2008)

Vegetation characteristics and eco-hydrological processes in a pristine mire in the Ob River valley (Western Siberia) - Aafke M. Schipper; Ron Zeefat; Franziska Tanneberger; Jeroen P. van Zuidam; Wulf Hahne; Sebastiaan A. Schep; Sander Loos; Wladimir Bleuten; Hans Joosten; Elena D. Lapshina; Martin J. Wassen (Plant Ecology, 2007)

Molecular epidemiology of enterovirus 71 over two decades in an Australian urban community - S. A. Sanders; L. J. Herrero; K. McPhie; S. S. W. Chow; M. E. Craig; D. E. Dwyer; W. Rawlinson; P. C. McMinn (Archives of Virology, 2006)

Physiological state of phytoplankton communities in the Southwest Atlantic sector of the Southern Ocean, as measured by fast repetition rate fluorometry - Claire L. Holeton; Florence Nédélec; Richard Sanders; Louise Brown; C. Mark Moore; David P. Stevens; Karen J. Heywood; Peter J. Statham; Cathy H. Lucas (Polar Biology, 2005)

Association of a functional BDNF polymorphism and anxiety-related personality traits - Undine E. Lang; Rainer Hellweg; Peter Kalus; Malek Bajbouj; Kirsten P. Lenzen; Thomas Sander; Dieter Kunz; Jürgen Gallinat (Psychopharmacology, 2005)

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Dichotomy between Lactobacillus rhamnosus and Klebsiella pneumoniae on dendritic cell phenotype and function - Henri Braat; Esther C. de Jong; Jan M. H. van den Brande; Martien L. Kapsenberg; Maikel P. Peppelenbosch; Eric A. F. van Tol; Sander J. H. van Deventer (Journal of Molecular Medicine, 2004)

Bone lamina thickness, bone apposition rates, and age estimates in sauropod humeri and femora - P. Martin Sander; Christian Tückmantel (PalZ, 2003)

Bioavailability of DON from natural and anthropogenic sources to estuarine plankton - Sybil P. Seitzinger; R. W. Sanders; Renée Styles (Limnology and Oceanography, 2002)
Utilization of dissolved organic nitrogen (DON) from natural (forests) and anthropogenic (animal pastures, urban/suburban storm water runoff) sources (three sites per source) by estuarine plankton communities was examined in spring, summer, and fall. The proportion of DON utilized ranged from 0 to 73%. Overall, urban/suburban storm water runoff had a higher proportion of bioavailable DON (59% ± 11) compared to agricultural pastures (30% 14) and forests (23% ± 19). DON bioavailability varied seasonally; however, the seasonal pattern differed for the three sources. Bacterial production increased linearly with the amount of DON utilized across all sources and seasons; the rate of increase was approximately five times greater per micromole of N as DON used relative to dissolved inorganic N (DIN) used. Although phytoplankton production generally increased with DON addition, the increased production was not correlated with the amount of DON utilized, suggesting that a variable portion of dissolved organic matter (DOM)‐N was directly or indirectly available to the phytoplankton. This indicates that phytoplankton production is not a good measure of the amount of bioavailable DON, and measurements of the amount of bioavailable DON based on bacterial responses alone might not reflect N available to phytoplankton. Preliminary seasonal budgets of bioavailable N (DIN plus bioavailable DON) as a function of land use suggest that ~80% of the total dissolved N (TDN) from urban/suburban runoff is bioavailable, whereas a lower proportion (20–60%) of TDN is bioavailable from forests and pastures. N budgets for aquatic ecosystems based on only DIN loading underestimate bioavailable N loading, whereas total N or TDN budgets overestimate bioavailable N inputs.

IgG and IgE immune response against the surface glycoprotein gp200 of Saccharomyces cerevisiae in patients with atopic dermatitis - P. Nenoff; Barbara Müller; U. Sander; G. Kunze; M. Bröker; U.-F. Haustein (Mycopathologia, 2001)

Bileaflet Aortic Valve Prosthesis Pivot Geometry Influences Platelet Secretion and Anionic Phospholipid Exposure - Brandon R. Travis; Ulla M. Marzec; Hwa Liang Leo; Takki Momin; Christine Sanders; Stephen R. Hanson; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2001)

Ichthyosauria: their diversity, distribution, and phylogeny - P. Martin Sander (PalZ, 2000)

An Intercomparison of NO2 and OClO Measurements at Arrival Heights, Antarctica during Austral Spring 1996 - R. W. Sanders; S. Solomon; K. Kreher; P. V. Johnston (Journal of Atmospheric Chemistry, 1999)

Atmospheric inputs of dissolved organic nitrogen stimulate estuarine bacteria and phytoplankton - S. P. Seitzinger; R. W. Sanders (Limnology and Oceanography, 1999)
Atmospheric deposition is recognized as a potentially large source of inorganic nutrients to many ecosystems. In marine systems, where nitrogen (N) is the nutrient typically limiting phytoplankton growth, rainwater is often a significant source of N. Although a considerable portion of atmospheric N deposition is in the form of organic N, only the inorganic N in rainwater has been considered by most previous studies. Laboratory experiments presented here indicate that dissolved organic nitrogen (DON) from rainwater can stimulate productivity of coastal marine bacteria and phytoplankton. A large percent of rainwater DON was potentially biologically available; 45–75% was rapidly utilized by the microorganisms. The magnitude of the response of bacterial and phytoplankton biomass to equivalent amounts of DON‐N or ammonium‐N was similar. However, the community composition of phytoplankton at the end of the experiment differed in treatments receiving DON and inorganic N. Diatoms and dinoflagellates accounted for >90% of the phytoplankton biomass in treatments receiving rainwater DON. In contrast, small (≪2 μm) monads accounted for >85% of the biomass in the treatments receiving ammonium. The results indicate that DON in rainwater can be an important source of N to ecosystems.

Variability in responses to nutrients and trace elements, and transmission of stressor effects through an estuarine food web - Denise L. Breitburg; James G. Sanders; Cynthia C. Gilmour; Colleen A. Hatfield; Richard W. Osman; Gerhardt F. Riedel; Sybil P. Seitzinger; Sybil P. Seitzinger (Limnology and Oceanography, 1999)
Aquatic systems are increasingly exposed to multiple stressors from anthropogenic sources. These stressors can vary in the consistency and magnitude of responses they elicit in biota and in how the presence of additional stressors modifies their effects. Understanding how the biological environment and temporal dynamics influence responses to stressors, and how stressors interact, is important to predicting their effects in the natural environment. We examined temporal variability in responses of an experimental estuarine food web to elevated trace elements and nutrients, as well as non‐additive effects of the combination of these two stressors. Experiments were conducted four times during spring through autumn 1996 in 20 l‐m3 mesocosms. We measured a range of system‐, population‐, and individual‐level parameters to quantify responses of phytoplankton, bacterioplankton, heterotrophic nanoflagellates, copepods, fish, and benthic invertebrates to trace element and nutrient additions. The response to trace element additions was more variable both temporally and among phytoplankton and higher trophic level taxa than was the response to nutrient additions. Most taxa increased, either significantly or showed a trend toward increasing, in response to nutrient additions in all four mesocosm runs. In contrast, the direction as well as the magnitude of responses to trace element additions varied considerably among taxa and experimental runs. Two distinct types of nutrient3trace element interactions were important. First, temporal dynamics of nutrient ratios appeared to affect the temporal pattern of toxicity of trace elements to phytoplankton. Second, in the June mesocosm run when trace element additions reduced production, abundance, or growth of many organisms, these reductions were often proportionately greater in nutrient addition tanks than where no nutrients were added. Our results suggest that considerable temporal and taxonomic variation in responses to trace element loadings are likely to be seen in field settings even under constant loadings to the system and that trace elements may mask the magnitude of the response to high nutrient loadings in eutrophic systems. More generally, the presence of multiple stressors may either increase or dampen the temporal and spatial variability seen in aquatic systems, depending on the interactions among stressors and the influence of background environmental conditions and sensitive species on the expression of stressor effects.

Tonoplast inorganic pyrophosphatase in Vicia faba guard cells - Catherine P. Darley; Lorna A. Skiera; Frederick D. Northrop; Dale Sanders; Julia M. Davies (Planta, 1998)

New finds ofOmphalosaurus and a review of Triassic ichthyosaur paleobiogeography - P. Martin Sander; Christiane Faber (PalZ, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Oxidative stress in silicosis: Evidence for the enhanced clearance of free radicals from whole lungs - Val Vallyathan; Stephen Leonard; Periannan Kuppusamy; Donna Pack; Michael Chzhan; Sherry P. Sanders; Jay L. Zweir (Molecular and Cellular Biochemistry, 1997)

Sequence variation in 5′ termini of rubella virus genomes: changes affecting structure of the 5′ proximal stem-loop - P. Johnstone; J. E. Whitby; T. Bosma; J. M. Best; P. G. Sanders (Archives of Virology, 1996)

The prevalence of antibodies to human T-lymphotropic virus type I in different population groups in Papua New Guinea - R. C. Sanders; P. M. Wai'in; S. S. Alexander; A. G. Levin; W. A. Blattner; M. P. Alpers (Archives of Virology, 1993)

HTLV-I antibody studies in villagers in East Sepik Province, Papua New Guinea - R. C. Sanders; A. Levin; G. Anian; I. Webber; H. Lee; P. Swanson; A. Diwan; R. Desowitz; W. A. Blattner; M. P. Alpers (Archives of Virology, 1990)

Molecular characterization of fetal antigens on red blood cells of chickens, Japanese quail, and quail-chicken hybrids - R. R. Dietert; D. P. Hartwell; K. Kline; B. G. Sanders (Biochemical Genetics, 1984)

The influence of mist irrigation on the potato IV. Tuber quality factors - D. C. Sanders; R. E. Nylund; E. C. Quisumbing; K. V. P. Shetty (American Journal of Potato Research, 1972)